DEVELOPMENT OF THE CONTENTS OF THE KEMUHAMMADIYAHAN LESSON PLAN IN THE UMSU ISLAMIC RELIGIOUS EDUCATION STUDY PROGRAM - Nurzannah, Nurzannah; Syamsuyurnita, Syamsuyurnita; Pasaribu, Munawir (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study was to find out and describe the content of the Kemuhammadiyahan lesson plan used in the Islamic Religious Education Study Program FAI UMSU. This type of research is analytic qualitative research. Data collection was carried out using document content analysis techniques and interviews. Data analysis uses an interactive analysis model that is carried out interactively and takes place. Continuously. Data research steps are carried out by data reduction, data display, and conclusion. The research results obtained were: 1) The contents of the lesson plans for the Kemuhammadiyahan course in the UMSU PAI Study Program were not tailored to the needs of graduates. All Basic Competencies that are formulated do not use operational verbs (OV). The methods listed in the Semester Lesson Plan (RPS) are still classical. The formulation of learning outcomes is at levels C1 and C2 with the LOTS category. 2) The contents of the syllabus for the Kemuhammadiyahan course in the PAI Study Program have not been developed according to the needs by adding several subjects from the Kemuhammadiyahan curriculum at the high school level. RPS development is carried out by formulating Basic Competency using operational verbs. The methods included must be able to trigger critical thinking, and reasoning skills, and be student-centered. The formulation of learning outcomes must be at the C3-C6 (HOTS) level.